Emotions in Korean Philosophy and Religion Confucian, Comparative, and Contemporary Perspectives - Chung, Edward Y. J.; Oh, Jea Sophia (Palgrave Studies in Comparative East-West Philosophy, 2022)
This pioneering book presents thirteen articles on the fascinating topic of emotions (jeong 情) in Korean philosophy and religion. Its introductory chapter comprehensively provides a textual, philosophical, ethical, and religious background on this topic in terms of emotions West and East, emotions in the Chinese and Buddhist traditions, and Korean perspectives. Chapters 2 to 5 of part I discuss key Korean Confucian thinkers, debates, and ideas. Chapters 6 to 8 of part II offer comparative thoughts from Confucian moral, political, and social angles. Chapters 9 to 12 of part III deal with contemporary Buddhist and eco-feminist perspectives. The concluding chapter discusses ground-breaking insights into the diversity, dynamics, and distinctiveness of Korean emotions. This is an open access book. Edward Y. J. Chung is Professor of Religious Studies, Asian Studies Director, and Korean Studies Project Director at the University ofPrince Edward Island, Charlottetown, Canada. Jea Sophia Oh is Associate Professor of Philosophy at West Chester University of Pennsylvania, USA. Her research primarily focuses on Asian and comparative philosophies, religion and ecology, and postcolonial theory. .